(untitled) (Journal of responsible AI & ethics, 2026)
The application of machine learning (ML) in various sectors such as healthcare, finance, and criminal justice has significantly transformed decision-making processes. However, the widespread use of ML algorithms has also brought attention to issues of bias and discrimination, which can perpetuate inequality and reinforce social biases. Fairness in machine learning has become a critical concern, as biased algorithms can result in discriminatory outcomes, especially when they are deployed in sensitive domains. This paper explores the different dimensions of fairness in ML, focusing on the sources of bias and the potential for discrimination in algorithmic decision-making. By reviewing recent research, theoretical models, and practical case studies, the paper aims to identify strategies and methodologies to mitigate bias and ensure the ethical use of machine learning technologies. It examines algorithmic fairness frameworks, such as individual fairness, group fairness, and causal fairness, and discusses the challenges in balancing accuracy with fairness. The study concludes with a set of recommendations for fairer machine learning practices, emphasizing the importance of transparency, accountability, and the inclusion of diverse perspectives in model development.